2008
DOI: 10.1111/j.1445-2197.2008.04687.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic‐assisted Skin‐sparing Mastectomy Combined With Sentinel Node Biopsy

Abstract: Breast-conserving surgery (BCS) has been carried out as desirable choice for patients with early-stage breast cancer. However, many patients obliged to abandon BCS because of tumours accompanied by extended intraductal components or multiple tumours. The purpose of this study was to develop a novel endoscopic-assisted technique for skin-sparing mastectomy (SSM) combined with sentinel node biopsy (SNB), followed by immediate breast reconstruction with mammary prosthesis. Between April 2000 and November 2006, 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 20 publications
2
48
0
Order By: Relevance
“…following an average follow-up duration of 24.1 months there was no reported LR [7,9,11,13,17,19,23,24]. However, notwithstanding some exceptions [17,24], the average duration of follow-up has been less than two years and investigators have observed LR following endoscopic resection when follow-up is extended beyond three years [15].…”
Section: Is Endoscopic Mastectomy Associated With An Increased Risk Omentioning
confidence: 99%
See 4 more Smart Citations
“…following an average follow-up duration of 24.1 months there was no reported LR [7,9,11,13,17,19,23,24]. However, notwithstanding some exceptions [17,24], the average duration of follow-up has been less than two years and investigators have observed LR following endoscopic resection when follow-up is extended beyond three years [15].…”
Section: Is Endoscopic Mastectomy Associated With An Increased Risk Omentioning
confidence: 99%
“…Ultra Retractor, HIROTECH retractor, Endoscopic Breast Retractor, etc) appears to significantly improve visualisation and aids dissection of the posterior aspect of the breast from the pectoralis fascia (see Figure 2) [7-9, 15-18, 22, 23, 25]. However, the successful use of balloon dissection has also been reported [10,24].…”
Section: Techniques For Endoscopic Posterior Breast Dissectionmentioning
confidence: 99%
See 3 more Smart Citations